The Danube – The Axis of European Security: Array - Iftode, Florin (Acta Universitatis Danubius. Relationes Internationales, 2020)
This article highlights some aspects of the Danube River which, in an increasingly dynamic Europe, offered good premisis for cooperation, and the sustainability of its borders has conferred, in general, stability and territorial strength of coastal states. However, this strength, over time, has unfavorably placed itself on the political convenience of the coastal states in terms of the geoeconomic dynamism of the riparian states. The European Union must meet the challenge of constantly adapting to the changes generated by internal factors (enlargement, aging, population growth and decline, the need to adapt the Union's institutions, efficiency, transparency and legitimacy of decision-making at Community level, communication with its citizens), as well as external (global economic and financial crisis, the crisis of natural resources and raw materials, the competition coming from the other poles of power and not only, the terrorist threat, the political instability in the states of North Africa, threats related to the environment such as climate change, natural disasters, pandemics, etc.). Due to the interference of economic and political interests, the Danube now represents a key point in the North Atlantic Alliance, facilitating access to the extended region of the Black Sea. We consider that the turbulent history of Europe has been closely linked to the legal regime of the Danube, and the chessboard of the players of political, diplomatic and economic interests has always reflected this issue. And as the river Danube is not a simple waterway, but a powerful base on the infrastructure of any interest, its problems must be fully understood.